Enhancing Analytical Thinking Skills and Scientific Attitudes of Prospective Science Teacher Students through Pre-Practicum Virtual Simulation - Nailil Inayah; Ahmad Lubab (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2023)
Analytical thinking skills are important for science pre-service teachers to achieve the professional competence of science educators. The aim of national education mandates the formation of a complete human being through the development of character and attitudes in the learning process, including a scientific attitude. Data shows that students' analytical thinking skills are still below standard and scientific attitudes have not been sufficiently trained in learning. The purpose of this research is to describe the analytical thinking skills and scientific attitude of prospective science teacher students through pre-practicum virtual simulation. The research design was a post-test-only control group design with a sample of 55 prospective science teacher students. The data was taken using an analytical thinking ability test and a scientific attitude questionnaire. The instruments used are worksheets and web-based simulations. The experimental class conducted a pre-practicum virtual simulation before the field practicum. The results of the Wilcoxon test were <0,05 showing differences in students’ analytical thinking skills through practicum and pre-practicum virtual simulation learning. The highest score of the analytical thinking skills indicator is ‘organizing’ namely 71,0 in the experimental class. Scientific attitude with the highest indicator is curiosity in the experiment and control class with percentages of 97% and 88% respectively. Overall, both analytical thinking skills and scientific attitude are enhanced through virtual simulation pre-practicum.